The Role of Influencer Credibility in Shaping Brand Trust on Social Media Platforms - Puspitasary, Bella Amillia Cindy; Dutahatmaja, Angga (International Conference of Innovation and Community Engagement, 2025)
In the digital marketing landscape, social media influencers play a pivotal role in shaping consumer perceptions and trust toward brands. This study investigates the extent to which influencer credibility—defined by expertise, trustworthiness, and attractiveness—impacts brand trust on social media platforms. By applying the Source Credibility Theory and brand trust frameworks, this research employs a quantitative survey method involving 300 active social media users who follow and engage with influencers across platforms such as Instagram, TikTok, and YouTube. The results demonstrate that influencer trustworthiness and expertise significantly influence consumer trust in associated brands, while attractiveness shows a moderate but context-dependent effect. Additionally, the perceived authenticity of influencer endorsements amplifies the positive relationship between credibility and brand trust. These findings highlight the strategic importance of selecting credible influencers to foster meaningful consumer-brand relationships. The study offers practical insights for marketers in optimizing influencer partnerships and underscores the ethical considerations in maintaining transparency and genuine advocacy in influencer-brand collaborations.